Prevalence and Characteristics of People with Disabilities Among Abused Victims in Saudi Arabia - Abdulaziz S. Alangari; Duaa Alammari; Norah Alhowaish; Waseemah Almutairi; Zainab Alnjeidi; Majid Aleissa (Springer, 2024)
Abstract Background Abuse is an ongoing public health issue that results in increased morbidity and mortality rates. Abuse against individuals with disabilities is a pervasive and deeply concerning issue, often compounded by factors of vulnerability and dependence. The majority of disabled individuals experience abuse, with the majority enduring it repeatedly. Identifying the problem is the first step towards preventing abuse. This study aimed to identify the prevalence of people with disabilities among abused victims and the victim's associated risk factors in Saudi Arabia. Methods This cross-sectional study obtained data from the National Family Safety Registry. All registered children and adults between April 2017 and December 2022 from 93 centers across 13 regions of Saudi Arabia were included. Logistic regression models were used to determine the association between independent variables and victim-related risk factors such as the onset of abuse complications, the victim being an adult or child, the victim's gender, and whether they had been previously abused. Results Individuals with disabilities comprise 1.4% (n = 199) of all reported cases of abuse (n = 14,004), and the trend of violence against people with disabilities has decreased during the 6-year study period. Of the abused people with disabilities, 72.4% were children, 57.8% were males, 45.2% were previously abused, and 65.3% had complications from the abuse. Caregiver type, perpetrator gender, perpetrator age, and previous abuse status were significant factors. Conclusions This study highlights the disability prevalence among reported abuse cases and evaluates victim's risk factors in Saudi Arabia, which demonstrates an urgency for targeted intervention and support. People with disabilities constitute a vulnerable demographic who require increased support and resources. Comprehensive data collection can be utilized for effective violence prevention strategies. Further research should explore qualitative methods and survey the rates of abuse among people with disabilities in the community to gain deeper insights.